PP.05.02: DIFFERENCE IN INTERARM BLOOD PRESSURE, CARDIOVASCULAR RISK FACTORS AND ORGAN DAMAGE IN TYPE 2 DIABETES. (June 2015) - Fedecostante, M.; Spannella, F.; Giulietti, F.; Ricci, M.; Pavani, M.; Espinosa, E.; Dessì-Fulgheri, P.; Bonfigli, A.R.; Boemi, M.; Sarzani, R.
Abstract : Objective: In type 2 diabetes mellitus (DM2) patients at high risk for atherosclerosis, we have examined the prevalence of an inter-arm difference of BP (IAD), its influence in hypertension detection and its association with cardiovascular risk factors and eGFR. Design and method: Height-hundred consecutive patients with DM2 and 213 controls selected on the basis of low cardiovascular risk or known severe peripheral arterial disease were studied with a validated device for simultaneous bilateral BP measurements. Association with eGFR was analyzed in a subgroup of 399 DM2 patients. Results: A prevalence of 43.6% for a systolic IAD >= 5 mmHg, 13.1% >= 10 mmHg and 4.8% >= 15 mmHg was found in DM2. More than 20% of DM2 patients were at risk for BP underestimation when the arm with lower-readings was taken. The most important baseline factors associated with increasing prevalence of IAD were higher BP (for each mmHg an OR from 1.014 to 1.021 depending by the IAD severity), dyslipidemia (OR 2.0) and smoking but only for an IAD >= 15 mmHg (OR: 2.6). The prevalence of systolic IAD increased with the overlapping of atherosclerosis risk factors. The expected association of higher BP with worsening eGFR was completely confirmed only when considering SBP values of the arm with higher readings. Conclusions: In conclusion, IAD prevalence is high in DM2, increasing with increasing atherosclerosis risk factors and is highly relevant for hypertension detection and management. Moreover, discordant data regarding the association of BP with organ damage is erroneously obtained if the arm with higher BP readings is not identified. These results should stimulate physicians and personnel involved with BP measurements to consider IAD carefully, especially in high risk patients.